Effects of Eye Drops Containing Hyaluronic Acid-Nimesulide Conjugates in a Benzalkonium Chloride-Induced Experimental Dry Eye Rabbit Model - Tzu-Yang Chen; Ching-Li Tseng; Chih-An Lin; Hua-Yang Lin; Parthiban Venkatesan; Ping-Shan Lai (MDPI AG, 2021)
Dry eye syndrome (DES) is a common ocular disease worldwide. Currently, anti-inflammatory agents and immunosuppressive drugs, such as cyclosporine A, have been widely used to treat this chronic condition. However, the multifactorial etiology of DES, poor tolerance, low bioavailability, and prolonged treatment to response time have limited their usage. In this study, nimesulide, a cyclooxygenase (COX)-2 selective inhibitor, was conjugated with hyaluronic acid (HA), and the HA-nimesulide conjugates were expected to increase the solubility and biocompatibility for alleviating the DES in the benzalkonium chloride (BAC)-induced goblet cell-loss dry eye model. The therapeutic efficacy of HA-nimesulide was assessed using fluorescein staining, goblet cell density by conjunctival impression cytology, and histology and immunohistochemistry of corneal tissues. Compared to commercial artificial tears and Restasis®, the HA-nimesulide conjugates could promote goblet cell recovery and enhance the regeneration of the corneal epithelium. Importantly, immunofluorescent staining studies demonstrated that the HA-nimesulide conjugates could decrease the number of infiltrating CD11b-positive cells after two weeks of topical application. In the anti-inflammatory test, the HA-nimesulide conjugates could inhibit the production of pro-inflammatory cytokines and prostaglandin E2 (PGE2) in the lipopolysaccharide (LPS)-stimulated Raw 264.7 cell model. In conclusion, we demonstrated that HA-nimesulide conjugates had anti-inflammatory activity, and promoted goblet cell recovery and corneal epithelium regeneration when used as topical eye drops; accordingly, the HA-nimesulide conjugates could potentially be effective for the treatment of DES.